Aperfeiçoamento de uma cabeça robótica com visão estereoscópica - Nunes, João Felipe Calvo (2009)
This paper presents enhancements in the mechanical design of a robotic head with stereo vision from a previous version. The methods used in the design and the results obtained are presented, as well as an overview of future research activities in the scope of the implementation of the robotic vision system as a whole.